Dual-modification of sago starch by gamma irradiation and annealing. Issue 1 (March 2021) - Lee, J-S; Jahurul, MHA; Fong, S-L
Abstract: Similar to other native starch, native sago starch found limited industrial applications due to its poor functional properties. Various modification methods may be employed to improve the properties, however, owing to the health concerns over chemical modification, this study was designed to modify sago starch using combination of two physical techniques – gamma irradiation and annealing (ANN). Native sago starch was first subjected to four doses of gamma radiation (5, 10, 25, 50 kGy) followed by annealing treatment. Measurement of pH, FTIR (Fourier Transform Infrared) analysis, characterization of pasting properties and thermal properties of the samples were performed. Irradiated samples contained shorter starch chains with higher mobility to effectively participate in the molecular realignment during ANN, resulted higher crystalline perfection and hence higher gelatinization temperature. The interactions and re-association of starch chains during ANN exerted significant change to the pH and functional properties of irradiated sago starch. Combining gamma irradiation at 5 and 10 kGy with annealing could potentially improve the heat and shear stability of sago starch. Dual-modification was also found able to improve the heat stability of sago starch without affecting the gelatinization enthalpy. These improved features can be beneficial to the sago-based food products that require high temperature processing.